Influência da maturação no rendimento de peito de frango marinado cozido em processo contínuo - Sartori, Tais Colpo (2012)
The objective of this study was to evaluate the influence of different ageing time after deboning (deboning time) and ageing time before deboning (holding time) in quality and cook loss of marinated, cooked and frozen chicken breast in continuous process. It was used experimental design 32 (3 deboning time: zero, 6 and 12 hours; and 3 holding time: zero, 12 and 24 hours), total of 9 treatments with 3 cooking repetition, total of 27 experiments. The breast fillets were marinated by tumbling, and brine was formulated with water and sodium chloride. It was evaluated brine absorption, thickness increase and weight loss during cooking, chicken breast pH, sensory analysis, shear force analysis and centesimal analysis of cooked and frozen chicken breast. Deboning time impacted in inicial pH, there was reduction between zero and 6 hours, time where chicken breast achieved rigor mortis resolution. There was an increase in pH with deboning time from 6 to 12 hours. In treatments with zero deboning time, it was observed a decrease in pH from zero to 12 hours, and an increase from 12 to 24 hours. Ageing time didn´t impact in brine absorption during tumbling. Ageing time, before and after deboning, influenced the cook loss, that was lower in fillets aged before deboning comparing to fillets aged after deboning. The increase in holding time from zero to 12 and 24 hours reduced cook loss, despite of deboning time. The influence of ageing on the fiber diameter during cooking was observed by significant increase on the thickness of chicken breast. Ageing times influenced sensory analysis as color, juiciness, flavor and tenderness, it was concluded that 6 hours before deboning were enough to achieve the desired tenderness. There was significant difference in shear force analysis between aged and not aged fillets. The best results for cooking loss and tenderness were achieved with deboning time of 6 or 12 hours, followed by holding time of 24 hours.